1983
DOI: 10.1136/bmj.286.6358.19
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine in hypertensive emergencies.

Abstract: The effects and safety of using oral nifedipine 10-20 mg as acute antihypertensive treatment were studied in a single-blind placebo-controlled study of 25 consecutive patients with very high blood pressure requiring emergency reduction. In addition the effect of this treatment on cerebral blood flow was investigated using xenon-133 in 10 patients randomly allocated to receive oral nifedipine or intravenous clonidine. Whereas placebo did not alter the blood pressure, oral nifedipine significantly reduced the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

1983
1983
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(41 citation statements)
references
References 11 publications
0
39
0
2
Order By: Relevance
“…43 One trial did not report any of the outcomes of interest (1 trial). 44 Two trials did not fulfil blood pressure threshold criteria. 45,46 One was a cross-over trial.…”
Section: Resultsmentioning
confidence: 99%
“…43 One trial did not report any of the outcomes of interest (1 trial). 44 Two trials did not fulfil blood pressure threshold criteria. 45,46 One was a cross-over trial.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, in the absence of detailed management guidelines and algorithms supported by data from the appropriate clinical trials, practitioners employ a number of diverse protocols, with quite varied results. [22][23][24][25][26][27][28][29][30][31][32][33] …”
Section: Introductionmentioning
confidence: 99%
“…An extra advantage of a calcium antagonist in comparison with other vasodilators might be, that it selectively increases cerebral and cardiac blood flow as has been shown in animal experiments (Aboul-Khair et al, 1981). Recently, Bertel et al (1983) demonstrated in five patients with severe hypertension, that cerebral blood flow remained constant or increased after emergency treatment with nifedipine. The observed increases in heart rate and the absence of an increase of the P-R interval were somewhat unexpected, since nifedipine has a direct negative chronotropic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients investigated until now had a normal renal function. Nifedipine has been used in only a few cases of hypertensive crisis (Murakami et al, 1972;Ueda et al, 1979;Bertel et al, 1983 iosonde 1217) from 30 min before until 60 min after the administration of nifedipine. With this device diastolic pressure is determined at a level comparable to Korotkoff sound V. Heart rates were calculated from ECG-strips taken immediately before and at 10 min intervals during 1 h after the nifedipine administration.…”
Section: Introductionmentioning
confidence: 99%